Real-Time Workload Scheduling (RTWS) Algorithm for Cloud - Nagaraju, Sabout; Parthiban, Latha (Journal of Information, 2015)
Cloud computing is the revenue gain and most advanced technology that has tremendous advantages over other technologies. It can be used as a utility for executing large size of real-time programs. These programs are decomposed into multiple inter-dependent tasks and executed on the multiple virtual processors where the open research issue is to be minimized make-span of the scheduling tasks. Our research aims to address this issue and degenerate the schedule length approximately equal to the available number of virtual processors. We proposed a real-time workload scheduling algorithm that does very well in reducing the number of initial clusters. The experimental results show that the execution times for various kinds of the DAGs can be reduced as much as possible and improves the performance of the early load scheduling algorithms for distributed cloud environment.